Preparation method of nano-silver-loaded hollow mesoporous hydroxyapatite, sodium carboxymethyl cellulose hydroxyapatite powder prepared by method, and nano-silver-loaded hollow mesoporous hydroxyapatite powder
The preparation of hollow mesoporous hydroxyapatite microspheres by hydrothermal synthesis and loading nanosilver is solved, and the problems of complex preparation and unstable effects of existing antibacterial materials are achieved, and the slow release and efficient antibacteriality of nanosilver are achieved, which is suitable for a variety of application scenarios.
Patent Information
- Application Number
- CN202510814145.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-06-18
- Publication Date
- 2025-07-18
- Estimated Expiration
- 2045-06-18
AI Technical Summary
The existing antibacterial materials have complex preparation process, high cost and unstable antibacterial effects. The nano-silver releases fast, making it difficult to maintain efficient antibacterial performance for a long time.
Hollow mesoporous hydroxyapatite microspheres were prepared by hydrothermal synthesis method, and nanosilver was modified with polyethyleneimine and electrostatically adsorbed nanosilver to form hollow mesoporous hydroxyapatite loaded nanosilver to achieve slow release and uniform distribution of nanosilver.
It achieves the slow and continuous release of nano silver, improves the durability and antibacterial effect of antibacterial materials, can effectively kill Gram-positive and negative bacteria, has good biocompatibility, and is suitable for a variety of fields.
Smart Images

Figure CN120323447A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the field of antibacterial materials, and specifically relates to a preparation method of hollow mesoporous hydroxyapatite loaded with silver nanoparticles, and carboxymethyl cellulose sodium hydroxyapatite powder, hollow mesoporous hydroxyapatite powder loaded with silver nanoparticles prepared by this method, and their applications. Background Art
[0002] Hydroxyapatite (HAP) is the main inorganic component of human bones and teeth. Due to its excellent biocompatibility, osteoconductivity, and bioactivity, it is widely used in bone repair, drug carriers, tissue engineering, environmental governance, and other fields. With the cross-development of materials science and biomedicine, the morphological control (such as microspheres, nanoparticles, etc.) and functionalization of HAP have become research hotspots. Among them, hollow mesoporous hydroxyapatite microspheres have attracted much attention due to their large specific surface area and hollow structure, which endow them with a large drug loading capacity and strong adsorption performance. For example, the invention patent application with the application number 201510351925.5 discloses a synthesis method of hollow hydroxyapatite, but the surface of the product is a spiky structure, and its specific surface area is smaller and its loading capacity is lower compared to the flower-like structure in this article. The invention patent application with the application number 202411603637X also discloses a kind of mesoporous hydroxyapatite microspheres regulated by malic acid, which is characterized in that: by controlling the concentration of the morphology regulator malic acid, adjusting the reaction time and temperature, the sphericity, particle size, surface micro-nano structure, crystallinity, etc. of the hydroxyapatite microspheres are adjusted. This regulation is relatively delicate and complex, with a large workload and is difficult to grasp.
[0003] Various surfaces in our daily life are vulnerable to the invasion of microorganisms (such as bacteria, viruses, etc.) from the air and solutions, which may then endanger human health. There are potential harmful bacteria everywhere around us. For example, speaking, coughing, sneezing, and even breathing can all generate water vapor droplets containing bacteria. Similarly, bacteria present in liquids (such as drinking water and hospital catheter liquids) can attach to the inner surfaces of blood vessels and pipes and grow and reproduce. When the cell number increases on the surface, microbial cells usually begin to form biofilms, which are composed of polysaccharide matrices embedding the cells. Such biofilms allow microbial cells to survive under harsh conditions, and the sensitivity of the embedded cells to most antibiotics and other biocides can be reduced by up to 1000 times, which may become a source of stubborn infections.
[0004] Traditional antibacterial materials include: natural antibacterial materials, organic antibacterial materials and inorganic antibacterial materials. Natural antibacterial materials are widely sourced, inexpensive, and have good biocompatibility and safety. However, their antibacterial activity is relatively low and their water solubility is poor, which limits their use in some application scenarios that require rapid dissolution and uniform dispersion. Organic antibacterial materials have a broad antibacterial spectrum and good antibacterial effects, but long-term use can easily cause bacteria to develop drug resistance, and they may also cause certain irritation to the human body during use. Inorganic antibacterial materials represented by metal oxides have high chemical stability and antibacterial durability. However, the antibacterial properties of these materials largely depend on their crystal structure and particle size, which are difficult to precisely control during the preparation process, resulting in unstable antibacterial effects. In addition, some inorganic antibacterial materials may pose potential hazards to the human body and the environment during use. Moreover, silver ions in traditional silver-based antibacterial materials also have the problem of being unstable and easily converting into silver oxide, making it impossible to maintain a high antibacterial level for a long time. Therefore, synthesizing nano silver for antibacterial purposes has the following advantages: strong antibacterial ability, broad antibacterial spectrum, long-lasting antibacterial effect, not easily generating drug resistance, strong penetration ability, low toxicity, and environmental friendliness, etc.
[0005] Hydroxyapatite is selected as the carrier, and antibacterial silver is loaded therein. For example, a patent published in 2020 provides a preparation method for a flaky hydroxyapatite carrier and a supported nano silver catalyst, which is characterized in that: first, flaky hydroxyapatite is synthesized, then it is soaked in a silver salt solution, and finally it is reduced in a hydrogen atmosphere to obtain the finished product. The abundant hydroxyl groups on the surface of hydroxyapatite enable it to be modified by other functional groups. However, this synthesis is relatively complex and requires many processes. Secondly, silver nitrate is used as a good silver salt solution, but the silver adsorbed by the impregnation method has a fast release rate and the effect is not lasting. For example, the invention patent with the application number CN201410619102.1 also discloses the preparation and application of an immunosensor in which silver ions replace calcium in hydroxyapatite, which is characterized in that: a certain proportion of silver nitrate solution and hydroxyapatite are mixed and continuously stirred to carry out an ion exchange reaction, and finally it is centrifuged and washed to make the finished product. The silver ions exchanged by this method are limited and can be completely released in a short period. If used in the antibacterial field, the antibacterial time is short and the effect is not lasting. Summary of the Invention
[0006] In view of the deficiencies of the background technology, the technical problem to be solved by the present invention is to provide a preparation method for hollow mesoporous hydroxyapatite loaded with nano silver. The synthesis process of this method is simple, easy to operate and has low cost. The finished product has better antibacterial properties. Its nano silver can slowly and continuously release silver ions, which can extend the antibacterial action time of nano silver and improve the durability of antibacterial materials.
[0007] A preparation method of hollow mesoporous hydroxyapatite microspheres loaded with silver nanoparticles, characterized in that the steps are as follows: Synthesize hollow mesoporous hydroxyapatite microspheres by hydrothermal synthesis method, then covalently modify polyethyleneimine onto the hollow mesoporous hydroxyapatite microspheres to form polyethyleneimine-hydroxyapatite, and then electrostatically adsorb negatively charged silver nanoparticles.
[0008] Preferably, the preparation of the hollow mesoporous hydroxyapatite microspheres includes the following steps: S1: Weigh anhydrous calcium chloride and sodium carboxymethylcellulose and disperse them separately in distilled water, and ultrasonically disperse them evenly; mix the two solutions and stir magnetically for 8 - 12 min; S2: Weigh anhydrous sodium carbonate and disperse it in distilled water. After dispersing evenly, quickly add it to the above mixed solution and continue stirring for 24 - 36 min; S3: After the reaction is completed, centrifuge and wash the precipitated substance with deionized water 2 - 3 times, and then wash it with absolute ethanol 2 - 3 times; S4: Place the precipitated substance in an oven and dry it at a temperature of 50°C - 70°C to obtain the prepared sodium carboxymethylcellulose-calcium carbonate microspheres, denoted as CMC-CaCO3; S5: Weigh disodium hydrogen phosphate dodecahydrate and dissolve it in distilled water. Add the above-prepared sodium carboxymethylcellulose-calcium carbonate microspheres to the solution. After ultrasonic homogenization, transfer the liquid to a polytetrafluoroethylene reaction kettle and carry out hydrothermal reaction at a temperature of 110°C - 170°C for 2.4 - 4 h; S6: After the polytetrafluoroethylene reaction kettle cools down, centrifuge and wash the precipitated substance with deionized water 2 - 3 times, and then wash it with absolute ethanol 2 - 3 times; S7: Place the precipitated substance in an oven and dry it at a temperature of 50°C - 72°C to obtain the prepared hollow mesoporous hydroxyapatite microspheres, denoted as CMC-HAP.
[0009] Preferably, the addition amount of calcium chloride powder in every 10 mL of calcium chloride solution is 1.11 g, the addition amount of sodium carboxymethylcellulose powder in every 10 mL of sodium carboxymethylcellulose solution is 60 mg; the addition amount of sodium carbonate powder in every 20 mL of sodium carbonate solution is 1.06 g; when the sodium carbonate solution is added to the mixed solution, the solution quickly turns into a milky white colloidal liquid; next, add 0.6 g of dry calcium carbonate powder to 15 mL of deionized water dissolving 5 g of disodium hydrogen phosphate dodecahydrate, stir evenly and transfer it to a polytetrafluoroethylene reaction kettle.
[0010] Preferably, the method for preparing polyethyleneimine-hydroxyapatite includes the following steps: S1: Weigh sodium carboxymethylcellulose-hydroxyapatite microsphere powder and ultrasonically disperse it in a centrifuge tube containing methanol solvent; S2: Weigh EDC, disperse it in an appropriate amount of methanol, add a small amount of triethylamine, mix well, transfer it to the above solution, and react on a shaker for 24 - 36 min; S3: Add methanol solution containing polyethyleneimine, continue to react on a shaker, and the total reaction time is 12 h; S4: After the reaction is completed, wash and centrifuge the product thoroughly with distilled water and absolute ethanol. After discarding the supernatant, put it into a vacuum drying oven to dry for standby. The obtained reaction product is polyethyleneimine-modified hydroxyapatite, denoted as CMC-HAP-PEI.
[0011] Preferably, 10 mL of methanol is added to every 500 mg of sodium carboxymethyl cellulose hollow mesoporous hydroxyapatite powder. The ratio of EDC to methanol and triethylamine is 1 g:5 mL:2.3 mL. 5 mL of methanol is added to every 250 mg of polyethyleneimine. After the reaction is completed, wash and centrifuge the product 2 - 3 times with distilled water and 2 - 3 times with absolute ethanol.
[0012] Preferably, the preparation method of the polystyrene sulfonate-coated silver nanoparticles includes the following steps: S1: Take silver nitrate and disperse it in distilled water to make a silver nitrate solution, and transfer it to a light-shielded conical flask; S2: Place the silver nitrate solution on a magnetic stirrer and stir, add the polystyrene sulfonate solution dropwise, and stir the adjusted solution for 30 min; S3: Weigh sodium borohydride and dissolve it in distilled water, and drop it into the above reaction system at a rate of 1 drop per 10 s, and continue to stir for 2 h; S4: After the reaction is completed, turn off the stirrer, and it can be stored in the dark for several months, denoted as Ag-PSS.
[0013] Preferably, the addition amount of every 46 mL of silver nitrate solution is 16.9 mg. The ratio of polystyrene sulfonate to distilled water is 30 μL:2 mL, and the ratio of sodium borohydride to distilled water is 3.78 mg:2 mL.
[0014] Preferably, the preparation method of the hollow mesoporous hydroxyapatite loaded with silver nanoparticles includes the following steps: S1: Weigh the polyethyleneimine-modified hydroxyapatite powder and ultrasonically disperse it in a centrifuge tube containing the silver nanoparticle solution; S2: Shake in the dark on a shaker for 6 h; S3: After the reaction is completed, wash and centrifuge several times with distilled water until the supernatant is colorless and transparent. After discarding the supernatant, put it into a vacuum drying oven to dry. The obtained reaction product is the hollow mesoporous hydroxyapatite loaded with silver nanoparticles, denoted as CMC-HAP-PEI@Ag.
[0015] The present invention also provides a sodium carboxymethyl cellulose hydroxyapatite powder, which is prepared by the above-mentioned preparation method.
[0016] The present invention also provides a hollow mesoporous hydroxyapatite powder loaded with nano silver, which is prepared by the above-mentioned preparation method.
[0017] Technical effects of the present invention: After adopting the above technical solution, calcium carbonate microspheres are firstly synthesized, and then hollow mesoporous hydroxyapatite microspheres are generated by a hydrothermal reaction using the calcium carbonate microspheres as a template. Due to the participation of sodium carboxymethyl cellulose, the product is negatively charged. Then, polyethyleneimine (PEI) is modified onto the hollow mesoporous hydroxyapatite microspheres in an organic solution, and the exposed amino groups make it positively charged. Then, negatively charged nano silver coated with sodium polystyrene sulfonate is synthesized. According to the principle of layer-by-layer assembly, nano silver is further loaded into the hollow mesoporous hydroxyapatite. The nano silver is evenly distributed, making the product have antibacterial and antiviral effects. The carrier also has a hollow structure and a mesoporous surface, with low density and a large specific surface area, enabling a high loading capacity and slow release. At the same time, it also has good biocompatibility and is an excellent carrier for loading nano silver.
[0018] Among them, nano silver mainly generates bactericidal activity by releasing silver ions. However, when bacteria directly contact the surface of the microspheres, the loaded nano silver may play a role by physically destroying the bacterial cell membrane or generating reactive oxygen species (ROS). The high specific surface area of the mesoporous structure also increases the contact probability between bacteria and the material surface. This material can be used to create a bactericidal surface. Such particles with contact and release of bactericidal activity can be evenly dispersed in polar / non-polar solvents, and thus are compatible with polar / non-polar film-forming matrices (such as TPU, PP, etc.). The solid surface formed after blending the two can effectively utilize the contact, release or synergistic mechanism of the two to kill bacteria, prevent the adhesion of bacteria on the surface, and prevent the formation of biofilms that are prone to cause infection events. This bactericidal surface has been proven to be able to kill most bacteria deposited on it through gas deposition and attached from aqueous solutions, including Gram-positive bacteria, Gram-negative bacteria, fungi, etc. Specifically, the antibacterial performance is evaluated by spraying an aqueous suspension of bacterial cells on the surface, then air-drying and counting the number of cells that remain viable (i.e., capable of growing colonies). The resulting surface can kill up to 99% of Gram-positive and Gram-negative bacteria deposited in aerosols or aqueous suspensions.
[0019] The present invention also provides the application of nano-silver-loaded hollow mesoporous hydroxyapatite in the preparation of antibacterial materials, antibacterial appliances or composite antibacterial films of organic polymers. Such antibacterial materials can serve as antibacterial coatings and be applied to paints, masks, and gas masks; they can be combined with organic polymer materials to form antibacterial composite materials; they can be combined with resins and applied to paint coatings; they can be combined with plastics and polymer resins and applied to filter meshes, outer shells of electrical appliances, food materials and transmission, reverse osmosis membranes, microfiltration membranes, ultrafiltration membranes, and nanofiltration membranes: they can be combined with silicone rubber and latex and applied to interventional catheters (such as cardiovascular and cerebrovascular interventional catheters, urinary catheters) and implantable catheters: they can also be combined with rubber and fibers and applied to clothing and masks; they can also be used to coat the surfaces of common objects (such as door handles, children's toys, computer keyboards, telephones, etc.) that people come into contact with in daily life, and can be used in medical consumables (such as urinary catheters, esophagus, tracheal intubation, etc.), textiles, coatings, packaging materials, etc., to make them antibacterial, so that they cannot spread bacterial infections. This material has a very wide range of application fields. Description of the Drawings
[0020] The present invention has the following drawings: Figure 1 It is a schematic diagram of the synthesis route of the hollow mesoporous hydroxyapatite microspheres and their nano-silver loading involved in the present invention; Figure 2 They are scanning electron microscope images of CaCO3 (a), CMC-CaCO3 (b), and CMC-HAP (c); Figure 3 They are Fourier transform infrared spectra of CaCO3 (a), CMC-CaCO3 (b), HAP (c), CMC-HAP (d), and CMC (e); Figure 4 They are X-ray diffraction patterns of CaCO3 (a), CMC-CaCO3 (b), and CMC-HAP (c); Figure 5 It is a transmission electron microscope image of CMC-HAP; Figure 6 They are N2 adsorption-desorption curves, specific surface area, and pore size distribution diagrams of CMC-HAP; Figure 7 They are Zeta diagrams of CMC-HAP-PEI, Ag-PSS, and CMC-HAP-PEI@Ag; Figure 8 They are X-ray diffraction patterns of CMC-HAP (a) and CMC-HAP-PEI@Ag (b); Figure 9 It is an elemental mapping diagram of CMC-HAP-PEI@Ag; Figure 10Cell viability graphs of CMC-HAP-PEI@Ag at different concentrations; Figure 11 Bacterial survival rates of Staphylococcus aureus (S. aureus), Escherichia coli (E. coli), Candida albicans (C. albicans), and methicillin-resistant Staphylococcus aureus (MRSA) treated with PBS phosphate buffer, different concentrations of CMC-HAP-PEI, and CMC-HAP-PEI@Ag; Figure 12 Growth of colonies of PBS phosphate buffer (a), CMC-HAP-PEI at 50 μg / ml (b); growth of various colonies of CMC-HAP-PEI@Ag at 1 μg / ml (c), 5 μg / ml (d), 10 μg / ml (e), 30 μg / ml (f), and 50 μg / ml (g); Figure 13 Virus titers of PRV virus in DMEM medium, CMC-HAP-PEI at 400 μg / ml and 500 μg / ml; virus titers of PRV virus in CMC-HAP-PEI@Ag at 400 μg / ml and 500 μg / ml. Detailed implementation manners
[0021] To further elaborate on the technical means and effects adopted by the present invention to achieve the predetermined invention purpose, the following describes in detail the specific implementation manners, structures, features, and effects of the present invention in combination with the accompanying drawings and preferred embodiments.
[0022] The preparation method of the hollow mesoporous hydroxyapatite microspheres loaded with silver nanoparticles provided by the present invention comprises the following steps: synthesizing hollow mesoporous hydroxyapatite microspheres by hydrothermal synthesis method, then covalently modifying polyethyleneimine (PEI) onto the hollow mesoporous hydroxyapatite microspheres to form polyethyleneimine hydroxyapatite, and then electrostatically adsorbing negatively charged silver nanoparticles.
[0023] The preparation of the hollow mesoporous hydroxyapatite microspheres in the above method comprises the following steps: S1: Weigh anhydrous calcium chloride and sodium carboxymethylcellulose and disperse them into distilled water respectively, and ultrasonically disperse them evenly; mix the two solutions and stir magnetically for 8 - 12 min, and the optimal magnetic stirring time is 10 min; S2: Weigh anhydrous sodium carbonate and disperse it into distilled water. After dispersing evenly, quickly add it to the above mixed solution and continue stirring for 24 - 36 min, and the optimal stirring time is 30 min; S3: After the reaction, centrifuge and wash the precipitated substance with deionized water 2 - 3 times, and then wash it with absolute ethanol 2 - 3 times; S4: Place the precipitated substance in an oven and dry it at a temperature of 50°C - 70°C (optimal temperature: 60°C) to obtain the prepared sodium carboxymethyl cellulose calcium carbonate microspheres, denoted as CMC-CaCO3. S5: Weigh disodium hydrogen phosphate dodecahydrate and dissolve it in distilled water. Add the above-prepared sodium carboxymethyl cellulose calcium carbonate microspheres (CMC-CaCO3) to the solution. After ultrasonic homogenization, transfer the liquid to a polytetrafluoroethylene reaction kettle and carry out hydrothermal reaction at a temperature of 110°C - 170°C (optimal temperature: 140°C) for 2.4 - 4 h. The optimal reaction time can be taken as 3 h. S6: After the polytetrafluoroethylene reaction kettle cools down, wash the precipitated substance formed by the reaction with deionized water by centrifugation 2 - 3 times, and then wash it with absolute ethanol 2 - 3 times. S7: Place the precipitated substance in an oven and dry it at a temperature of 50°C - 72°C (optimal temperature: 60°C) to obtain the prepared hollow mesoporous hydroxyapatite microspheres (i.e., sodium carboxymethyl cellulose hydroxyapatite), denoted as CMC-HAP.
[0024] In the above steps, the addition amount of calcium chloride powder in every 10 mL of calcium chloride solution is 1.11 g, the addition amount of sodium carboxymethyl cellulose powder in every 10 mL of sodium carboxymethyl cellulose solution is 60 mg; the addition amount of sodium carbonate powder in every 20 mL of sodium carbonate solution is 1.06 g; when the sodium carbonate solution is added to the mixed solution, the solution quickly turns into a milky white colloidal liquid; next, add 0.6 g of dry calcium carbonate powder to 15 mL of deionized water dissolving 5 g of disodium hydrogen phosphate dodecahydrate, stir evenly and then transfer it to a polytetrafluoroethylene reaction kettle.
[0025] The above method for preparing polyethyleneimine hydroxyapatite includes the following steps: S1: Weigh the sodium carboxymethyl cellulose hydroxyapatite microsphere powder (CMC-HAP) and ultrasonically disperse it in a centrifuge tube containing methanol solvent. S2: Weigh EDC, disperse it in an appropriate amount of methanol, add a small amount of triethylamine, mix evenly, transfer it to the above solution, and react on a shaker for 24 - 36 min (optimal reaction time: 30 min). S3: Add methanol dissolving polyethyleneimine (PEI), and continue to react on a shaker for a total time of 12 h. S4: After the reaction is completed, thoroughly wash and centrifuge the product with distilled water and absolute ethanol. After discarding the supernatant, put it into a vacuum drying oven to dry for standby. The drying temperature can be taken as 60°C. The obtained reaction product is polyethyleneimine-modified hydroxyapatite, denoted as CMC-HAP-PEI.
[0026] In the above steps, 10 mL of methanol is added to every 500 mg of sodium carboxymethyl cellulose hollow mesoporous hydroxyapatite powder (CMC-HAP). The ratio of EDC to methanol and triethylamine is 1 g: 5 mL: 2.3 mL. 5 mL of methanol is added to every 250 mg of polyethyleneimine (PEI). After the reaction is completed, the product is washed and centrifuged 2-3 times with distilled water and 2-3 times with absolute ethanol.
[0027] The method for preparing the above-mentioned polystyrene sulfonate-coated silver nanoparticles includes the following steps: S1: Take silver nitrate and disperse it in distilled water to make a silver nitrate solution, and transfer it to a light-shielded conical flask. S2: Place the silver nitrate solution on a magnetic stirrer and stir at a stirring speed of 300 rpm min -1) , add the polystyrene sulfonate solution dropwise, and stir the adjusted solution for 30 min. S3: Weigh sodium borohydride and dissolve it in distilled water, and drop it into the above reaction system at a speed of 1 drop per 10 s, and continue to stir for 2 h. S4: After the reaction is completed, turn off the stirring, and it can be stored in the dark for several months, denoted as Ag-PSS.
[0028] In the above steps, the addition amount of every 46 mL of silver nitrate solution is 16.9 mg. The ratio of polystyrene sulfonate to distilled water is 30 μL: 2 mL, and the ratio of sodium borohydride to distilled water is 3.78 mg: 2 mL.
[0029] The method for preparing the above-mentioned hollow mesoporous hydroxyapatite loaded with silver nanoparticles includes the following steps: S1: Weigh polyethyleneimine-functionalized hydroxyapatite (CMC-HAP-PEI) powder and ultrasonically disperse it in a centrifuge tube containing silver nanoparticle solution (Ag-PSS). S2: Shake it in the dark on a shaker for 6 h. S3: After the reaction is completed, centrifuge and wash it several times with distilled water until the supernatant is colorless and transparent. After discarding the supernatant, put it into a vacuum drying oven and dry it at a drying temperature of 60 °C. The obtained reaction product is hollow mesoporous hydroxyapatite loaded with silver nanoparticles, denoted as CMC-HAP-PEI@Ag.
[0030] In the above steps, 30 mL of silver nanoparticle solution (PSS-Ag) is added to every 300 mg of polyethyleneimine-functionalized hydroxyapatite powder. After the reaction is completed, the material is washed and centrifuged with distilled water until the supernatant is colorless.
[0031] The present invention discloses a sodium carboxymethyl cellulose hydroxyapatite powder, which is in the form of a white powder, and its preparation steps are as follows: S1: Weigh anhydrous calcium chloride and sodium carboxymethylcellulose and disperse them separately in distilled water, and disperse them evenly by ultrasonic wave; mix the two solutions and stir magnetically for 8 - 12 min (the optimal magnetic stirring time is 10 min). S2: Weigh anhydrous sodium carbonate and disperse it in distilled water. After dispersing evenly, quickly add it to the above - mentioned mixed solution and continue stirring for 24 - 36 min (the optimal stirring time is 30 min). S3: After the reaction ends, wash the precipitated substance generated by the reaction with deionized water by centrifugation for 2 - 3 times, and then wash it with absolute ethanol for 2 - 3 times. S4: Place the precipitated substance in an oven and dry it at a temperature of 50℃ - 70℃ (the optimal temperature is 60℃), then the prepared sodium carboxymethylcellulose calcium carbonate microspheres are obtained, denoted as CMC - CaCO3. S5: Weigh disodium hydrogen phosphate dodecahydrate and dissolve it in distilled water. Add the above - prepared sodium carboxymethylcellulose calcium carbonate microspheres (CMC - CaCO3) to the solution. After ultrasonic dispersion, transfer the liquid to a polytetrafluoroethylene reaction kettle and carry out hydrothermal reaction at a temperature of 110℃ - 170℃ (the optimal temperature is 140℃) for 2.4 - 4 h (the optimal reaction time is 3 h). S6: After the polytetrafluoroethylene reaction kettle cools down, wash the precipitated substance generated by the reaction with deionized water by centrifugation for 2 - 3 times, and then wash it with absolute ethanol for 2 - 3 times. S7: Place the precipitated substance in an oven and dry it at a temperature of 50℃ - 72℃ (the optimal temperature is 60℃), then the prepared hollow mesoporous hydroxyapatite microspheres (i.e., sodium carboxymethylcellulose hydroxyapatite) are obtained, denoted as CMC - HAP.
[0032] In the above steps, the addition amount of calcium chloride powder in every 10 mL of calcium chloride solution is 1.11 g, the addition amount of sodium carboxymethylcellulose powder in every 10 mL of sodium carboxymethylcellulose solution is 60 mg; the addition amount of sodium carbonate powder in every 20 mL of sodium carbonate solution is 1.06 g; when the sodium carbonate solution is added to the mixed solution, the solution quickly becomes a milky white colloidal liquid; next, add 0.6 g of dry calcium carbonate powder to 15 mL of deionized water dissolving 5 g of disodium hydrogen phosphate dodecahydrate, stir evenly and then transfer it to a polytetrafluoroethylene reaction kettle.
[0033] The sodium carboxymethylcellulose hydroxyapatite powder material disclosed by the present invention is a micron - sized material with a hollow mesoporous micro - spherical morphology, and can be applied to the following fields: a. Drug delivery field: drug slow - release and controlled - release, protecting drug activity; b. Medical aesthetics field: as a carrier to load growth factors, promoting skin repair and regeneration, and can also be used as a filling material; c. Orthopedic field: can be used as a scaffold material for bone tissue engineering; d. Dental field: can load periodontal growth factors or antibacterial drugs for the repair and regeneration of periodontal tissues, and can also be used for the surface modification of dental implants.
[0034] A kind of hollow mesoporous hydroxyapatite powder loaded with nano silver provided by the present invention is in the form of a light yellow powder, and its preparation steps are as follows: S1: Weigh the polyethyleneimine modified hydroxyapatite (CMC-HAP-PEI) powder and ultrasonically disperse it in a centrifuge tube containing the nano silver solution (Ag-PSS); S2: Oscillate in the dark on a shaker for 6 h; S3: After the reaction, centrifuge and wash several times with distilled water until the supernatant is colorless and transparent. After discarding the supernatant, put it into a vacuum drying oven (60 °C) to dry. The obtained reaction product is the hollow mesoporous hydroxyapatite loaded with nano silver, denoted as CMC-HAP-PEI@Ag; In the above steps, 30 mL of nano silver solution (PSS-Ag) is added to every 300 mg of polyethyleneimine modified hydroxyapatite powder. After the reaction is completed, the material is washed and centrifuged with distilled water until the supernatant is colorless.
[0035] In the above preparation method, anionic polymers such as heparin, hyaluronic acid, and sodium alginate can be used to replace sodium carboxymethyl cellulose, and the addition amount is 50-80 mg. The rest of the reaction is the same as that of sodium carboxymethyl cellulose.
[0036] The above hollow mesoporous hydroxyapatite powder loaded with nano silver can be used in the preparation of antibacterial materials or antibacterial appliances or in the composite antibacterial film of organic polymers by applying the hollow mesoporous hydroxyapatite powder loaded with nano silver. Among them, antibacterial materials: dental restoration materials, bone repair materials, etc. The composite materials made can be used for the coatings of dental and orthopedic filling materials or implants. The material is compounded with a biodegradable polymer to make a porous scaffold for bone defect repair. Antibacterial appliances: Coating this composite material on the surfaces of surgical instruments, catheters, implantable devices, etc. can reduce the risk of postoperative infection. Organic polymers: Adding the material to thermoplastic polyurethane to make an antibacterial film; compounding it with polymers such as polyethylene and polypropylene to make an antibacterial packaging film.
[0037] The technical steps of the present invention are described one by one based on the following attached drawings: Refer to Figure 1 As shown, the present invention provides a simple preparation method for hollow mesoporous hydroxyapatite, and the steps are as follows: I. Preparation of sodium carboxymethyl cellulose calcium carbonate (CMC-CaCO3): Weigh 1.11 g of anhydrous calcium chloride and disperse it in 10 ml of distilled water. Weigh 60 mg of sodium carboxymethyl cellulose and disperse it in 10 ml of distilled water. Mix the two and ultrasonically homogenize them, then magnetically stir at room temperature for 10 min (rotation speed 800 rpm). After stirring evenly, quickly add 1.06 g of anhydrous sodium carbonate dispersed in 20 ml of distilled water, and continue to stir at room temperature for 30 min (rotation speed 800 rpm). After the reaction is completed, wash the product with deionized water and absolute ethanol three times each to remove the unreacted part, and dry it in an oven at 60 °C to obtain sodium carboxymethyl cellulose calcium carbonate microspheres, denoted as CMC-CaCO3.
[0038] II. Preparation of sodium carboxymethyl cellulose hydroxyapatite (CMC-HAP): Weigh 5 g of disodium hydrogen phosphate dodecahydrate and disperse it in 15 ml of distilled water, and ultrasonically disperse it evenly. Weigh 0.6 g of CMC-CaCO3 from the above reaction product and add it to this solution, and continue to ultrasonically disperse it evenly. Then transfer the liquid to a polytetrafluoroethylene reaction kettle and react at 140 °C for 3 h. After the polytetrafluoroethylene reaction kettle cools down, wash it with deionized water and absolute ethanol three times each to remove the unreacted part, and then dry it in an oven at 60 °C to obtain sodium carboxymethyl cellulose hydroxyapatite powder. Sodium carboxymethyl cellulose hydroxyapatite is in the form of a white powder, denoted as CMC-HAP.
[0039] The obtained product was characterized by scanning electron microscopy (SEM). Figure 2 SEM images of CaCO3 (a), CMC-CaCO3 (b), and CMC-HAP (c). It can be clearly observed from Figure 2 that under the action of sodium carboxymethyl cellulose, the morphology of calcium carbonate changes from a rhombus to a microsphere shape, and then the surface of the hydroxyapatite formed by hydrothermal reaction is a mesoporous structure. The results show that the preparation of mesoporous hydroxyapatite is successful.
[0040] The present invention was characterized by Fourier transform infrared spectrometer (FTIR). Figure 3 FTIR spectra of CaCO3 (a), CMC-CaCO3 (b), HAP (c), and CMC-HAP (d). Curve a is the infrared spectrum of CaCO3. From the structure of inorganic substances, when CMC is not contained, most of the particles are calcite aggregates; a peak at 745 cm -1 appears in curve b, which is the characteristic bending vibration peak of vaterite, and 712 cm -1 is the in-plane bending vibration peak of aragonite, while 874 cm -1is the out-of-plane bending vibration peak of calcite's carboxyl group. Therefore, b represents the doping state of calcite, aragonite, and vaterite. The cd curve is the FTIR spectrum of HAP, which conforms to the corresponding peak positions, proving the successful synthesis of hydroxyapatite. In addition, a peak at 1640 cm -1 appears in the d curve, which conforms to the stretching vibration peak of the carboxyl C=O double bond of CMC in the e curve, proving the existence of CMC in HAP.
[0041] The obtained product was characterized by X-ray diffraction pattern (XRD). Figure 4 are the X-ray diffraction patterns of CaCO3 (a), CMC-CaCO3 (b), and CMC-HAP (c). In the absence of CMC, the diffraction peaks (012), (104), (110), (113), (202), (018), and (116) corresponding to the a graph are the diffraction peaks of CaCO3 calcite. In the presence of CMC, in addition to the diffraction peaks of calcite, the other peaks in the b graph (004), (110), (112), (114), and (300) indicate the existence of spherical crystals, which means that the crystal is composed of calcite and aragonite vaterite; at the same time, the diffraction peaks in the b graph are significantly shifted towards a higher θ angle, indicating the doping of organic matter and proving the existence of CMC. Only the characteristic peaks of hydroxyapatite are shown in the c graph, indicating that there is no CaCO3 residue. The broad peak is due to the low crystallinity of the formed apatite. The detected structure is very similar to that of biological apatite, indicating the successful synthesis of hydroxyapatite.
[0042] The microstructure of the obtained product was observed by transmission electron microscopy (TEM). It can be seen that the product is a microsphere with a diameter of about 3-5 μm and has a hollow structure. Thus, the successful synthesis of hollow mesoporous hydroxyapatite microspheres was confirmed.
[0043] The mesoporous structure of the obtained product and the corresponding BJH pore size distribution curve were further demonstrated by nitrogen adsorption-desorption isotherms. CMC-HAP can be confirmed as a type-IV isotherm with an H3-type hysteresis loop. The H3-type hysteresis loop does not show restricted adsorption at high P / P0 because the aggregation of particles leads to the formation of slit-shaped pores, which can also be seen from the TEM images. By analyzing the adsorption-desorption isotherm, the BET surface area and pore volume of CMC-HAP were calculated to be 24.5908 m 2 / g and 0.114585 cm 3 / g, respectively. The average pore size of the BJH is a single peak of 18.6387 nm. These nanopores greatly increase its specific surface area and biological activity, making it better applicable to fields such as drug slow release.
[0044] III. Preparation of Polyethyleneimine Hydroxyapatite (CMC-HAP-PEI): Weigh 500 mg of the above-synthesized sodium carboxymethyl cellulose-hydroxyapatite (CMC-HAP), 1 g of EDC, and 250 mg of polyethyleneimine (PEI), disperse them in 20 ml of methanol, then add 2.3 ml of triethylamine, and react on a shaker (180 rpm) for 12 h. After the reaction, the product is washed three times with deionized water and anhydrous ethanol respectively to remove the unreacted part, and then dried in an oven at 60 °C to obtain hollow mesoporous hydroxyapatite covalently grafted with PEI, denoted as CMC-HAP-PEI.
[0045] IV. Preparation of polystyrene sulfonate-coated silver nanoparticles (AgNPs-PSS): Weigh 16.9 mg of silver nitrate, place it in a 100 mL conical flask protected from light, add 46 ml of distilled water and dissolve it by ultrasonic treatment. Take 30 μl of polystyrene sulfonate (PSS), add it to 2 mL of distilled water, disperse it evenly by ultrasonic treatment, and then add it dropwise to the silver nitrate solution. Stir magnetically at a speed of 300 r min -1 for 30 min. Weigh 3.8 mg of sodium borohydride, dissolve it completely in 2 mL of distilled water, and then slowly add it dropwise to the above reaction system. As the sodium borohydride solution is added, the mixed solution quickly changes from colorless to yellowish brown. Continue to stir at a speed of 300 r min -1 for 2 h. Then a silver nanoparticle solution coated with PSS is obtained, denoted as Ag-PSS.
[0046] V. Preparation of hollow mesoporous hydroxyapatite loaded with silver nanoparticles (CMC-HAP-PEI@Ag): Weigh 100 mg of the dried CMC-HAP-PEI material into a centrifuge tube, add 10 mL of the above AgNPs-PSS solution, and react under dark conditions with shaking at room temperature for 6 h. After the reaction, centrifuge (8000 r min-1, 3 min), discard the upper yellow liquid until the washing liquid becomes colorless to remove the AgNPs-PSS that has not been loaded onto the material, and dry it at 60 °C overnight to obtain a hollow mesoporous hydroxyapatite material loaded with silver nanoparticles, which is in the form of a pale yellow powder, denoted as CMC-HAP-PEI@Ag.
[0047] The obtained product is characterized by zeta potential. Figure 7The zeta potential diagrams of CMC-HAP, CMC-HAP-PEI, Ag-PSS, and CMC-HAP-PEI@Ag are shown. Since there are a large number of imino groups on polyethyleneimine, the potential of the particles changes from -20 mV to 24.9 mV before and after the modification of polyethyleneimine. The synthesized silver nanoparticles are negatively charged due to the coating of sodium polystyrene sulfonate, with a potential of -36.3, and the potential of the final loaded product is 3.83. The results indicate that the preparation of hollow mesoporous hydroxyapatite loaded with silver nanoparticles is successful.
[0048] The obtained products were characterized by X-ray diffraction pattern (XRD). Figure 8 The XRD patterns of CMC-HAP-PEI and CMC-HAP-PEI@Ag are shown. The peaks of silver element are (111), (200), and (220) in the figure. The detected structure is extremely similar to that of silver element, indicating the successful loading of silver nanoparticles.
[0049] The obtained products were characterized by mapping in transmission electron microscopy. Figure 9 The element mapping diagram of hollow mesoporous hydroxyapatite loaded with silver nanoparticles is shown. It can be seen from the figure that silver element is evenly distributed on the surface of the material. The results indicate that the preparation of hollow mesoporous hydroxyapatite loaded with silver nanoparticles is successful.
[0050] The obtained products were detected for their cytotoxicity by cck-8 kit. Figure 10 The relationship diagram between material concentration and cell survival rate is shown. It can be seen from the figure that when the material concentration is 500 μg / ml or less, the cell survival rate is greater than 90%, proving that it is within the biosafety concentration range at this concentration and below.
[0051] Verification of technical effects: The antibacterial tests of CMC-HAP-PEI and CMC-HAP-PEI@Ag prepared by the above preparation method were carried out on Staphylococcus aureus, Escherichia coli, Candida albicans, and methicillin-resistant Staphylococcus aureus. The samples were incubated with 6 CFU mL -1 of bacterial suspension in PBS phosphate buffer for 24 h, and then 100 μL of the suspension was spread on solid medium and cultured for 24 h; after incubation at 37 °C for 24 h, the colonies on the agar medium were counted. The bacterial survival rate was defined as the colony-forming unit on the agar plate relative to the control group. A bacterial suspension of 6 CFU mL -1 in PBS phosphate buffer was used as the blank control.
[0052] The experimental results are shown in Figures 11 - 13, CMC-HAP-PEI did not have an obvious antibacterial effect at the microgram dose, while the bacterial killing rate of the CMC-HAP-PEI@Ag group was 99%. The lethal dose for Staphylococcus aureus was 50 μg / ml, for Escherichia coli was 5 μg / ml, for Candida albicans was 50 μg / ml, and for methicillin-resistant Staphylococcus aureus was 10 μg / ml.
[0053] The present invention demonstrates a method for constructing hollow mesoporous hydroxyapatite microspheres loaded with silver nanoparticles, which kill bacteria through the loaded silver nanoparticles. Here, the antibacterial effect and antibacterial spectrum are verified through strains such as Staphylococcus aureus, Escherichia coli, Candida albicans, and methicillin-resistant Staphylococcus aureus. The results prove that the hollow mesoporous hydroxyapatite loaded with silver nanoparticles has good antibacterial effects. On the one hand, the high specific surface area and porous structure of the hollow mesoporous material enable it to adsorb more bacteria, enrich the bacteria around the material, thereby increasing the contact opportunity between silver nanoparticles and bacteria and improving the antibacterial efficiency. On the other hand, under the loading of the hollow mesoporous material, the antibacterial mechanism of silver nanoparticles may be further optimized. Silver nanoparticles can not only release silver ions to interfere with the physiological functions of bacteria, but also directly contact with the bacterial cell membrane to destroy the structure and integrity of the cell membrane, thereby inhibiting the growth and reproduction of bacteria. This synthesis method has a simple process, low cost, and wide application range; it has good antibacterial persistent stability and reusability; the synthesized product has high biosafety and can be applied to fields such as orthopedics, dentistry, and medical aesthetics, which will also greatly promote the development of the antibacterial field.
[0054] The above are only the preferred embodiments of the present invention, and do not impose any form of limitation on the present invention. Although the present invention has been disclosed above with preferred embodiments, it is not intended to limit the present invention. Any person skilled in the art can make some modifications or equivalent changes to the above-disclosed technical content within the scope of the technical solution of the present invention. However, as long as it does not depart from the technical solution content of the present invention, any brief modifications, equivalent changes, and modifications made to the above embodiments based on the technical essence of the present invention still fall within the scope of the technical solution of the present invention.
Claims
1. A method for preparing hollow mesoporous hydroxyapatite microspheres loaded with silver nanoparticles, characterized in that: the steps As follows: Hollow mesoporous hydroxyapatite microspheres are synthesized by a hydrothermal synthesis method, and then polyethyleneimine is covalently modified onto the hollow mesoporous hydroxyapatite microspheres to form polyethyleneimine hydroxyapatite, and then negatively charged silver nanoparticles are electrostatically adsorbed.
2. The preparation method of the hollow mesoporous hydroxyapatite microspheres loaded with silver nanoparticles according to claim 1, characterized in that: The preparation of the hollow mesoporous hydroxyapatite microspheres includes the following steps: S1: Weigh anhydrous calcium chloride and sodium carboxymethylcellulose and disperse them separately in distilled water, and ultrasonically disperse them evenly; mix the two solutions and stir magnetically for 8 - 12 min; S2: Weigh anhydrous sodium carbonate and disperse it in distilled water. After dispersing evenly, quickly add it to the above mixed solution and continue stirring for 24 - 36 min; S3: After the reaction is completed, centrifuge and wash the precipitated substance with deionized water 2 - 3 times, and then wash it with absolute ethanol 2 - 3 times; S4: Place the precipitated substance in an oven and dry it at a temperature of 50°C - 70°C to obtain the prepared sodium carboxymethylcellulose calcium carbonate microspheres, denoted as CMC-CaCO3; S5: Weigh disodium hydrogen phosphate dodecahydrate and dissolve it in distilled water. Add the above-prepared sodium carboxymethylcellulose calcium carbonate microspheres (CMC-CaCO3) to the solution. After ultrasonic homogenization, transfer the liquid to a polytetrafluoroethylene reaction kettle and carry out a hydrothermal reaction at a temperature of 110°C - 170°C for 2.4 - 4 h; S6: After the polytetrafluoroethylene reaction kettle cools down, centrifuge and wash the precipitated substance with deionized water 2 - 3 times, and then wash it with absolute ethanol 2 - 3 times; S7: Place the precipitated substance in an oven and dry it at a temperature of 50°C - 72°C to obtain the prepared hollow mesoporous hydroxyapatite microspheres, denoted as CMC-HAP.
3. The preparation method of the hollow mesoporous hydroxyapatite microspheres loaded with silver nanoparticles according to claim 2, characterized in that: The addition amount of calcium chloride powder in every 10 mL of calcium chloride solution is 1.11 g, and the addition amount of sodium carboxymethylcellulose powder in every 10 mL of sodium carboxymethylcellulose solution is 60 mg; the addition amount of sodium carbonate powder in every 20 mL of sodium carbonate solution is 1.06 g; when the sodium carbonate solution is added to the mixed solution, the solution quickly turns into a milky white colloidal liquid; next, add 0.6 g of dry calcium carbonate powder to 15 mL of deionized water dissolving 5 g of disodium hydrogen phosphate dodecahydrate, stir evenly and transfer it to a polytetrafluoroethylene reaction kettle.
4. The preparation method of the hollow mesoporous hydroxyapatite microspheres loaded with silver nanoparticles according to claim 1, characterized in that: The method for preparing polyethyleneimine hydroxyapatite includes the following steps: S1: Weigh sodium carboxymethylcellulose hydroxyapatite microsphere powder and ultrasonically disperse it in a centrifuge tube containing methanol solvent; S2: Weigh EDC, disperse it in an appropriate amount of methanol, add a small amount of triethylamine, mix evenly, transfer it to the above solution, and react on a shaker for 24 - 36 min; S3: Add methanol dissolving polyethyleneimine and continue to react on a shaker, with a total reaction time of 12 h; S4: After the reaction is completed, thoroughly wash and centrifuge the product with distilled water and absolute ethanol. After discarding the supernatant, place it in a vacuum drying oven to dry for standby. The obtained reaction product is polyethyleneimine-modified hydroxyapatite, denoted as CMC-HAP-PEI.
5. The preparation method of the hollow mesoporous hydroxyapatite microspheres loaded with silver nanoparticles according to claim 4, characterized in that: Add 10 mL of methanol to every 500 mg of sodium carboxymethyl cellulose hollow mesoporous hydroxyapatite powder. The ratio of EDC to methanol and triethylamine is 1 g:5 mL:2.3 mL. Add 5 mL of methanol to every 250 mg of polyethyleneimine. After the reaction is completed, wash and centrifuge the product 2 - 3 times with distilled water and 2 - 3 times with absolute ethanol.
6. The preparation method of the hollow mesoporous hydroxyapatite microspheres loaded with silver nanoparticles according to claim 1, wherein: The preparation method of polystyrene sulfonate - coated silver nanoparticles comprises the following steps: S1: Take silver nitrate and disperse it in distilled water to make a silver nitrate solution, and transfer it to a light - proof conical flask. S2: Place the silver nitrate solution on a magnetic stirrer and stir, add the polystyrene sulfonate solution dropwise, and stir the adjusted solution for 30 min. S3: Weigh sodium borohydride and dissolve it in distilled water, and drop it into the above reaction system at a rate of 1 drop every 10 s, and continue to stir for 2 h. S4: After the reaction is completed, turn off the stirrer. It can be stored in the dark for several months, denoted as Ag - PSS.
7. The preparation method of the hollow mesoporous hydroxyapatite microspheres loaded with silver nanoparticles according to claim 6, characterized in that: The addition amount of every 46 mL of silver nitrate solution is 16.9 mg. The ratio of polystyrene sulfonate to distilled water is 30 μL:2 mL, and the ratio of sodium borohydride to distilled water is 3.78 mg:2 mL.
8. The preparation method of the hollow mesoporous hydroxyapatite microspheres loaded with nano silver according to claim 1, characterized in that: The preparation method of the hollow mesoporous hydroxyapatite loaded with silver nanoparticles comprises the following steps: S1: Weigh the polyethyleneimine - modified hydroxyapatite powder and ultrasonically disperse it in a centrifuge tube containing the silver nanoparticle solution. S2: Oscillate in the dark on a shaker for 6 h. S3: After the reaction is completed, centrifuge and wash with distilled water several times until the supernatant is colorless and transparent. After discarding the supernatant, put it into a vacuum drying oven to dry. The obtained reaction product is the hollow mesoporous hydroxyapatite loaded with silver nanoparticles, denoted as CMC - HAP - PEI@Ag.
9. A sodium carboxymethyl cellulose hydroxyapatite powder, characterized in that: Prepared by using the preparation method described in claim 2 or 3.
10. A hollow mesoporous hydroxyapatite powder loaded with silver nanoparticles, characterized in that: Prepared by using the preparation method described in claim 8 or 9.
Citation Information
Patent Citations
Preparation and application of an immunosensor in which silver ions replace calcium in hydroxyapatite
CN104374908B
Hollow hydroxyapatite microsphere and preparation method thereof
CN104961115A
Method for in-situ preparing nano-silver compound bactericide
CN102657228A
Functional graphene oxide loaded nano-silver antibacterial material as well as preparation method and application thereof
CN104472538A
Spherical hollow hydroxyapatite particle and preparation method thereof
CN104909346A